Sistemática e biogeografia de besouros curculionídeos (Curculionoidea; Coleoptera) associados a figueiras (Ficus; Moracae) - Rocha, Luciano Palmieri (2017)
Among the number of examples of broad radiations of insects on plants, the fig fig wasp system is one of the most remarkable. Although this interaction has frequently been used as a model for studies of mutualism and coevolution, other groups of insects associated with fig trees have received less attention. The weevils (Coleoptera: Curculionidae) associated with figs are one notable example. Being the largest family of animals, weevils achieved great evolutionary success due to their early association with their host plants. Despite few reports in literature, there is strong evidence of the specialization of weevils on figs. The main objective of this thesis was to understand how diversification of Curculionidae took place in fig trees. Previous studies have never addressed the systematics and biogeography of fig weevils under a phylogenetic framework. Therefore, we analyzed the tempo of diversification of Curculionidae lineages that use fig trees as host in order to reconstruct their historical biogeography. To gather information on fig weevils, we collected 325 fruit sets from more than 12% of the total Ficus species, from the Neotropical, Afrotropical and Oriental regions. We also examined seven entomological collections (AMNH, BMNH, INBIO, MNHN, MZUSP, NMNH, SAMC) searching for weevil specimens collected on figs. At least 80 weevil species from five genera (Cetatopus, Omophorus, Carponinus, Curculio, and Indocurculio) were found to be associated with figs. The radiation of curculionids on figs occurred at least three times independently. The tempo of diversification of the crown fig weevils is congruent with the diversification of figs during the Upper-Cretaceous/Lower-Eocene period. We hypothesize that the variation of the sea level and warmer climate in the past had great influence on the evolution of the species. Our results encourage future research on the biology and ecology of these species and will help us to understand the role weevils may have played in the evolution of the fig- fig wasp mutualism.